2021
DOI: 10.1016/j.jds.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relationship between maxillary sinus membrane thickening and the adjacent teeth health by cone-beam computed tomography

Abstract: Background/purpose Maxillary posterior teeth have close anatomical proximity to the maxillary sinus floor. The aim of this retrospective study was to evaluate the associations between maxillary sinus membrane thickening and the adjacent teeth health by cone-beam computed tomography (CBCT). Materials and methods CBCT images were collected from 235 Taiwanese patients. The sinus mucosal thickening >2 mm is considered a pathologic sinus membrane. Demographic data such as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
6
14
0
3
Order By: Relevance
“…The response of the sinus membrane to periapical pathology, endodontic treatments and periodontitis can be diverse, although apical infections, and especially periodontitis, play a greater role in the development of sinus thickening, in line with the article published in 2021 by Huang et al [ 53 ], who found a significant association with bone loss and periapical radiolucency. The anatomical condition of the interrelation of the roots with the floor of the maxillary sinus seems to be a key element and has been mentioned by different authors, who report a significant association between the proximity of the diseased tooth roots to the sinus and the prevalence of disease of the sinus [ 5 , 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 56%
“…The response of the sinus membrane to periapical pathology, endodontic treatments and periodontitis can be diverse, although apical infections, and especially periodontitis, play a greater role in the development of sinus thickening, in line with the article published in 2021 by Huang et al [ 53 ], who found a significant association with bone loss and periapical radiolucency. The anatomical condition of the interrelation of the roots with the floor of the maxillary sinus seems to be a key element and has been mentioned by different authors, who report a significant association between the proximity of the diseased tooth roots to the sinus and the prevalence of disease of the sinus [ 5 , 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, the risk of MS abnormality was significantly higher in the presence of PAL (9,(17)(18)21,(28)(29)(30)(31)(32), consistent with our results. The resolution of MS abnormalities after root canal treatment of a PAL tooth has been reported (33), which confirmed the correlation between PAL and MS abnormalities.…”
Section: Discussionsupporting
confidence: 93%
“…These differences are due to different definitions of 'periodontitis' from one study to another, with some including all and others only severe periodontitis. The probability of MS abnormalities increases as PBL worsens, and severe PBL is associated with MS abnormalities (9,24,29,36), consistent with our study. Mucosa thickening was reduced within 4 months with thorough debridement after tooth extraction in units with severe PBL (34), further confirming the correlation between severe PBL and MS abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Yaş ortalamaları 43,18±16,13 olan 235 hasta üzerinde yapılan bir çalışmada, mukoza kalınlığı 2 mm'den daha fazla olan sinüs oranı %36,6 bulunmuştur. 33 Dört yüz on sinüs mukozası üzerinde yapılan bu çalışmada ise 122 tane sinüs mukozasının (%29,8) ise 2 mm'den kalın olduğu tespit edilmiştir Phothikhun ve ark.nın 250 sinüs KIBT görüntüleri üzerinde gerçekleştirdiği çalışmada, 146 sinüste (%29,2) düz, 50 sinüste (%10) polipoid mukozal kalınlaşma bildirmiştir. 25 Çalışmamızdaki toplam 410 sinüs KIBT görüntülerinde 44 (%10,7) düz, 78 (%19,02) polipoid kalınlaşma tespit edildi.…”
Section: Discussionunclassified